Garcilaso and Peralta: one history, two interpretations - Quiroz Chueca, Francisco (2009)
This article presents an analysis of the work of two founders of Peruvian historiography: Inca Garcilaso de la Vega and Pedro Peralta Barnuevo. The historical work of Garcilaso and Peralta shows competition that characterizes Peruvian historiography from its very beginnings since their visions opposse and exclude each other. Indeed, while early in the seventeenth century Garcilaso created a version that emphasizes Incan and Encomendero role in Peruvian history with Cuzco as the center of the Andean civilization, a century later Peralta presents his own version stressing Lima as the historical heart of Peru in a history where Creoles are the protagonists of the forging of the Peruvian nationality. A counterpoint between these two ways of historical interpretation allows us to better evaluate the origins of such contradictory images in force in Peruvian historiography for centuries to come. This article shows too the political bases of the historical ideas of both Garcilaso and Peralta.